Nutritional Status of Children Under Five Year of Age in Anganwadi Centers in Kolar Area Of Madhya Pradesh - Shailendra Meena; Rituja Kaushal; D M Saxena (Medsci Publications, 2015)
Objectives: This study has been designed to calculate the preva- lence of malnutrition and it's association with various epidemio- logical determinants in a given interventional area. Methodology: It is a community based cross sectional study. House to house survey was conducted and necessary data was collected by interviewing mothers and other care takers. Anthro- pometric measurements and clinical examination were done to assess the nutritional status of the of the under five age group children. Result: As per new WHO child growth standards it was found that 51% of under five children had varying degree of malnutri- tion. On the basis of clinical examination the prevalence of malnu- trition was 49%. Around 40% of the children above one year of age had mid arm circumference of less than 13.5 cm. In our study certain variables like family size, total number of children in the family, parental level of education, mother's employment, moth- er's age of marriage, personal health & hygiene related factors as well as child feeding & rearing practices were found to be signifi- cantly associated with reduction in malnutrition. Conclusion: In spite of presence of interventional centres in urban slums, malnutrition prevalence remain at older rate. So a multi pronged approach is needed to further rectify the situation.